Thermal Diffusivity Study on Clay From Benin By "Flash Method” - AGOUA, EUSÈBE (My University, 2015)
Knowledge of thermophysical parameters of local materials of construction has been essential when one considered the fast development of the market of building and especially the need for saving energy while ensuring the thermal comfort in housing. This work aimed to measure one of these parameters, the diffusivity, with an instrumentation based on “Flash Method”. It presented the results of measurement of the thermal diffusivity of dry clay and saturated clay, at different rates of cement, the clay has been taken in South of Benin. The results showed that the thermal diffusivity of dry samples was always lower than those of saturated samples. The first was about 0.468x10-6m2/s whereas the second was about 0.496 x10-6m2/s. In the two cases, the values confirmed that the clay is good to be used as building and construction material.
Keywords: Clay - Cement - Stabilization - Thermal Diffusivity - “Flash Method”